2018
DOI: 10.1371/journal.pntd.0006792
|View full text |Cite
|
Sign up to set email alerts
|

Phospho-proteomic analysis of primary human colon epithelial cells during the early Trypanosoma cruzi infection phase

Abstract: The protozoan parasite Trypanosoma cruzi, the causative agent of Chagas disease, causes severe morbidity and mortality in afflicted individuals. About 30% of T. cruzi-infected individuals present with cardiac, gastrointestinal tract, and/or neurological disorders. Megacolon, one of the major pathologies of Chagas disease, is accompanied by gastrointestinal motility disorders. The molecular mechanism of T. cruzi-mediated megacolon in Chagas disease is currently unknown. To decipher the molecular mechanism of T.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 58 publications
1
18
0
Order By: Relevance
“…We showed that T. cruzi upregulates the levels of TSP-1 during the process of infection [19,34]. Others showed that TSP-1 is one of the downstream molecules of the hippo signaling cascade [22,25].…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…We showed that T. cruzi upregulates the levels of TSP-1 during the process of infection [19,34]. Others showed that TSP-1 is one of the downstream molecules of the hippo signaling cascade [22,25].…”
Section: Discussionmentioning
confidence: 88%
“…Furthermore, we also showed that the parasite interacts with host TSP-1 through T. cruzi calreticulin (TcCRT) located on the surface of the parasite [18]. The preincubation of host cells with an inhibitor of janus kinase (JNK) which is upstream of TSP-1, reduced the upregulation of TSP-1 induced by the parasite during the early phase of infection, indicating that TSP-1 upregulation is important and plays an essential role during infection [19]. The host cell signaling mechanism(s) regulated by the expressed host TSP-1 to facilitate infection and T. cruzi mediated pathogenesis remains to be elucidated.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…It has been widely demonstrated that NF-κB is involved in the pro-inflammatory response in different models of T. cruzi infection (15,29,31,57,58). This transcriptional factor regulates the expression of several pro-inflammatory cytokines and chemokines such as TNFα, IL-1β, IL-6, and FIGURE 9 | Schematic representation of the pro-angiogenic and anti-inflammatory actions of HP 24 in T. cruzi-infected macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…In T. cruzi -infected macrophage cultures, an increase in c-Jun phosphorylation was similarly observed [51]. Likewise, significant up-regulation of c-Jun was detected in early T. cruzi infection of primary human colonic epithelial cells by phosphoproteomics and Western blot [55]. In addition, primary cultures of cardiac myocytes displayed an increase in nuclear translocation of JunB up to 2 h after T. cruzi infection [56].…”
Section: Discussionmentioning
confidence: 99%